A opção pelos pobres: Do Concílio Vaticano II ao Papa Leão - Zanini, Rogério (Revista Eclesiástica Brasileira, 2026)
Refletir sobre a esperança dos pobres segundo a fé cristã constitui uma urgência devido a percepção do retrocesso em marcha contra os pobres na Igreja e na sociedade hoje. Este estudo tem como objetivo revisitar e reafirmar a opção preferencial pelos pobres por meio de uma pesquisa de caráter teórico-bibliográfico. A reflexão se desenvolve em quatro momentos: inicialmente, analisa a relação do Concílio Vaticano II com a opção pelos pobres; em seguida, examina como essa opção se tornou central nas quatro Conferências do Episcopado Latino-Americano; posteriormente, avalia como o Papa Francisco aborda essa temática em seu magistério; por fim, reafirma-se que a opção pelos pobres é uma dimensão constitutiva do ser cristão, evidenciando sua necessidade e atualidade na vida eclesial. Os resultados esperados apontam para a reafirmação de que “fora dos pobres não há salvação”, pois os pobres constituem um “quid substancial”, não sendo uma realidade periférica ou secundária no cristianismo. Conforme Mt 25, os pobres são o critério de discernimento da evangelização e do juízo escatológico. Abstract: Reflecting on the hope of the poor from the perspective of Christian faith is an urgent task, given the perceived setbacks currently affecting the poor both in the Church and in society. This study aims to revisit and reaffirm the preferential option for the poor through a theoretical and bibliographic research approach. The reflection unfolds in four stages: initially, it analyzes the relationship between the Second Vatican Council and the option for the poor; next, it examines how this option became central in the four Conferences of the Latin American Episcopate; subsequently, it evaluates how Pope Francis addresses this theme in his magisterium; finally, it reaffirms that the option for the poor is a constitutive dimension of being Christian, highlighting its necessity and relevance in ecclesial life. The expected results point to the reaffirmation that “outside the poor there is no salvation,” as the poor constitute a quid substancial -not a peripheral or secondary reality in Christianity. According to Matthew 25, the poor are the criterion for discerning evangelization and the eschatological judgment. Keywords: Second Vatican Council; Liberation Theology; Option for the Poor; Pope Francis.